المصارف الإسلامية وقدرتها على جذب الودائع دراسة تحليلية للمصارف الإسلامية في الجمهورية العربية السورية - صيّوح, لؤي; غيّا, دانيا (Latakia University Journal - Economic and Legal Sciences Series, 2015)
تعد المصارف الإسلامية جزءاً هاماً من النظام المصرفي حيث حازت على ثقة العملاء وأثبتت نجاحها وقدرتها على المنافسة خلال العقد الماضي. انطلاقاً من ذلك تناولت هذه الدراسة مفهوم المصارف الإسلامية وتطورها وأهدافها. وركزت على الودائع (كمصدر خارجي أساسي لأموال المصارف الإسلامية) من حيث تعريفها وأبرز أنواعها ثم ناقشت قدرة المصارف الإسلامية على جذب الودائع المالية من خلال دراسة حجم الودائع ونموها عبر التحليل المالي للبيانات المالية للمصارف الإسلامية السورية وهي (البنك الدولي الإسلامي، بنك الشام الإسلامي، بنك البركة الإسلامي) وذلك خلال الفترة (2009 – 2013). وقد توصلت هذه الدراسة لعدد من النتائج كان أبرزها أن المصارف الإسلامية حظيت بإقبال كبير بدليل التطور الواضح في حجم الايداعات خلال المدة المدروسة. كما أوصت الدراسة بأهمية زيادة الوعي الادخاري والعمل على جذب شرائح مختلفة من المتعاملين في سورية. The Islamic Banks are an important part of the banking system, which have earned the trust of customers and proven their success and ability to compete over the past decade. Thus, this study offers the concept of Islamic banks and its development and targets. It also focuses on deposits (as important source of external founds for Islamic bank) in terms of concept and types. This study also discusses the ability of Islamic banks to attract financial deposits through studying the volume of deposits and their evaluation through financial analysis of the annual financial statement of the Syrian Islamic banks (International Islamic Bank, al-Baraka Islamic Bank, Sham Islamic Bank) during the period 2009-2013. As the study found a number of results, the most important was that Islamic Banks have received highly sought clear evidence of evolution in the volume of the deposits during the period study. The study also recommended increasing awareness of the importance of savings and work to attract different segments of the dealers in Syria.